Using the Cluster Method in Education System - Shadmanbekova Kamola Abdulazizovna (International Journal on Integrated Education, 2023)
In Uzbekistan state of politics priority from directions one as in development problems has been of children early social adaptations issues defined. New education policy done increase important strategic mechanism as education institutions study to the cluster combine issues seeing will be released.